2018
DOI: 10.1186/s12889-018-6038-9
|View full text |Cite
|
Sign up to set email alerts
|

Public health response to large influx of asylum seekers: implementation and timing of infectious disease screening

Abstract: BackgroundInfectious disease screening of migrants at increased risk is a feature of national infection prevention and control measures. Asylum seekers in Finland are offered screening of tuberculosis (TB), hepatitis B, human immunodeficiency virus infection (HIV) and syphilis based on individual risk assessment. We aimed to evaluate the public health response to a large influx of asylum seekers to Finland in 2015–2016 with respect to national guidelines on initial health services and infectious disease screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Our findings show that many migrants accessing emergency services may be missing out on screening for infectious diseases, aligning with previous research and discourse from other EU/EEA countries, despite agreement that it is beneficial [ 10 , 38 , 54 , 55 ]. Routine testing for new entrants from high-incidence countries is recommended for LTBI, HIV, and hepatitis B and C in a range of clinical and community settings [ 22 , 23 , [56] , [57] , [58] ].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings show that many migrants accessing emergency services may be missing out on screening for infectious diseases, aligning with previous research and discourse from other EU/EEA countries, despite agreement that it is beneficial [ 10 , 38 , 54 , 55 ]. Routine testing for new entrants from high-incidence countries is recommended for LTBI, HIV, and hepatitis B and C in a range of clinical and community settings [ 22 , 23 , [56] , [57] , [58] ].…”
Section: Discussionsupporting
confidence: 89%
“…During the peak of immigration in 2015/2016, thus far unprecedented numbers of refugees and asylum seekers were a challenge for receiving health care systems [10]. In this context, screening for tuberculosis (TB) offered the opportunity to provide appropriate treatment of this severe infectious disease [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…TB-prevalence ranged from 0.26 to 0.05% in a study by Herzmann et al, including screening results from 4, both rural and metropolitan centers in Germany 2015 [19] but difficulties with the arrangement of follow up examinations were reported. The need for data collection and analysis in order to improve screening algorithms has been addressed by several authors [9,10,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the prevalence of HBV was less amongst undocumented women in this study than what Wendland et al [17] had found (6,5 %; N=92). In addition, this study showed that undocumented pregnant women had higher prevalence of HIV and HBV compared with asylum seekers in Finland (HIV: 0,3 %; n=45, HBV: 1,6 %; n=275) [41] and higher prevalence of HIV and syphilis compared with asylum seekers in Italy (HIV: 1,6 %; n=5, syphilis: 0,7 %; n=2) [42].…”
Section: Screening Of Infectionsmentioning
confidence: 65%